IMPLEMENTASI PERLINDUNGAN HAK ANAK PASCA PERCERAIAN DI KOTA PAREPARE PERSPEKTIF HUKUM ISLAM - Rasida; Basri, Rusdaya; Said, Zainal; Aris; Saidah (IAIN BONE, 2025)
Divorce has significant implications for the fulfillment of children’s rights, particularly custody, financial support, and education. This study examines the implementation of child rights protection after divorce in Parepare City and its conformity with Islamic legal principles. Employing a qualitative juridical-empirical approach, data were collected through interviews with Religious Court judges, the Child Protection Agency, and families affected by divorce, and analyzed in reference to the Child Protection Law, the Compilation of Islamic Law, and the views of Islamic jurists. The findings indicate that child rights protection has not been optimally implemented due to low legal awareness among parents, weak institutional supervision, and limited access to basic rights for children. From the perspective of Islamic law, protecting children after divorce remains a moral and religious obligation of parents. Therefore, synergy among state institutions, religious leaders, and society is essential to ensure the fulfillment of children’s rights in accordance with Islamic values and statutory regulations.